Bacterial population study in oil-contaminated and uncontaminated soils - Hadry Nordin, Noor Faizul Hadry; Tg Mahassan, Tg Shilatul Hirwany; Khan Chowdhury, Ahmed Jalal (Zibeline International Publishing, 2018)
Soil provides a vital habitat primarily for bacteria to continue the process of biogeochemical cycle. The remarkable metabolic diversity and capacity of the soil bacteria is increasingly being harnessed for the benefit of humankind. One of the beneficial spin-offs from the understanding of the metabolism of soil microbes is the development of bioremediation for contaminated soils. Investigation on bacterial diversity was conducted on several types of samples for both contaminated and uncontaminated soils. The soil texture test determined that the soil samples obtained were sandy, silt and clay, respectively. The microbial population were enumerated using colony counting while bacteria characterisation and identification were performed using Gram staining, morphological and biochemical analysis. This study indicated that microbial population is higher in hydrocarbon-contaminated soils compared to uncontaminated soils. On the other hands, the bacterial diversity is lower in contaminated soils compared to uncontaminated soils. The study also portrays that Gram-positive bacteria, Staphylococcus spp was dominant in untreated soils while Gram negative bacteria, Pseudomonas spp was dominant genus in hydrocarbon contaminated soil.